LEVEL OF ACQUISITION OF ENTREPRENEURIAL INNOVATION SKILLS BY POSTGRADUATE BUSINESS EDUCATION STUDENTS FOR SELF-SUSTAINABILITY IN RIVERS STATE (NAU Journal of Technology and Vocational Education, 2024)
The study ascertained the level of acquisition of entrepreneurial innovation skills by postgraduate business education students for self-sustainability in Rivers State. One researchquestion aided the study and one hypothesis was tested at 0.05 level of significance. The designof the study was descriptive survey. A total of 298 business education postgraduate students intwo Rivers State universities made up the population. 44 postgraduate business educationstudents in Rivers State University and 254 postgraduate business education students in IgnatiusAjuru University of Education in Rivers State. The instrument for data collection was astructured questionnaire tittled: Entrepreneurial Innovation Skills Acquisition Questionnaire(EISAQ). Three experts validated the instrument and a reliability test using Cronbach Alphamethod yielded an internal consistency index of 0.86. Mean ratings and standard deviationwere used to answer the research question while t-test for large group mean was used to test thehypothesis at a significance at 0.05. The findings of the study revealed that business educationpostgraduate students acquired moderate level of entrepreneurial innovation, skills for selfsustainability. The findings of the study also revealed that postgraduate business educationstudents in Rivers State University and Ignatius Ajuru University of Education did not differsignificantly regarding the level of acquisition of entrepreneurial innovation skills for selfsustainability. Based on the findings, conclusion was drawn that entrepreneurial innovationskills acquired by postgraduate business education students for self-sustainability wasnecessary. Lack or absence of these skills negatively affected graduates embarking on anybusiness ventures was led to business failures. It was recommended among others that graduatestudents of business education must be able to maintain entrepreneurial characteristics andtraits by finding solution to problems that arise when operating business ventures. The courageto continue the business will lead to success and self-sustainability. Entrepreneurship centres inuniversities or other tertiary institutions in Nigeria must be equipped and utilized to assistinstitutions to bridge the gap created by the theoretical nature of entrepreneurial programmes ininstitutions.
Keywords: Skills, Entrepreneurial innovation skills, Business education, Acquisition, Selfsustainability